Can nontriggered thoracic CT be used for coronary artery calcium scoring? A phantom study. Issue 8 (18th July 2013) - Xie, Xueqian; Greuter, Marcel J. W.; Groen, Jaap M.; de Bock, Geertruida H.; Oudkerk, Matthijs; de Jong, Pim A.; Vliegenthart, Rozemarijn
Abstract : Purpose: : Coronary artery calcium score, traditionally based on electrocardiography (ECG)‐triggered computed tomography (CT), predicts cardiovascular risk. However, nontriggered CT is extensively utilized. The study‐purpose is to evaluate the in vitro agreement in coronary calcium score between nontriggered thoracic CT and ECG‐triggered cardiac CT. Methods: : Three artificial coronary arteries containing calcifications of different densities (high, medium, and low), and sizes (large, medium, and small), were studied in a moving cardiac phantom. Two 64‐detector CT systems were used. The phantom moved at 0–90 mm/s in nontriggered low‐dose CT as index test, and at 0–30 mm/s in ECG‐triggered CT as reference. Differences in calcium scores between nontriggered and ECG‐triggered CT were analyzed by t ‐test and 95% confidence interval. The sensitivity to detect calcification was calculated as the percentage of positive calcium scores. Results: : Overall, calcium scores in nontriggered CT were not significantly different to those in ECG‐triggered CT ( p > 0.05). Calcium scores in nontriggered CT were within the 95% confidence interval of calcium scores in ECG‐triggered CT, except predominantly at higher velocities (≥50 mm/s) for the high‐density and large‐size calcifications. The sensitivity for a nonzero calcium score was 100% for large calcifications, but 46% ± 11% for small calcifications in nontriggered CT. Conclusions: : When performing multiple measurements, good agreement in positive calcium scores is found between nontriggered thoracic and ECG‐triggered cardiac CT. Agreement decreases with increasing coronary velocity. From this phantom study, it can be concluded that a high calcium score can be detected by nontriggered CT, and thus, that nontriggered CT likely can identify individuals at high risk of cardiovascular disease. On the other hand, a zero calcium score in nontriggered CT does not reliably exclude coronary calcification.